Teleworking of School Libraries Belonging to the Regional Directorate of Heredia, Circuit 04 During the Covid-19 Pandemic - Ruiz Bustos, Ana Priscilla (Innovaciones Educativas, 2025)
Librarians had to adapt teleworking to school libraries in order to support the educational center in the learning process of students. This study was carried out in 2020 with librarians of school libraries of Circuit 04 of the Regional Directorate of Heredia. The research design was carried out by means of a questionnaire applied in the first quarter of 2020 to librarians from six educational centers that have a formal code for libraries of Circuit 04 of the Regional Directorate of the province of Heredia. It was found that virtual platforms are fundamental for direct communication between students, teachers and librarians. The different tasks performed by those who worked in school libraries during the pandemic were also identified. The use of technological tools to develop school library activities was a challenge.